Biomonitoring coastal environments with transplanted macroalgae: A methodological review. (October 2018) - García-Seoane, R.; Aboal, J.R.; Boquete, M.T.; Fernández, J.A.
Abstract: The use of macroalgae transplants is a recent technique used in pollution biomonitoring studies in marine ecosystems. Only 60 articles published between 1978 and 2017 reported the use of this environmental tool for the active biomonitoring of inorganic pollutants and nutrients worldwide. In this review paper, we evaluated studies on this topic in relation to the development of methodological aspects of the technique and the degree of standardization of the protocols used. On the basis of findings of this review, we conclude that the technique is not yet standardized and that uniformisation of protocols is required to enable comparison of the results of different studies. We propose a new protocol for applying the technique, in which each suggestion has been carefully and rigorously compared with the relevant findings reported in the available literature. Graphical abstract: Highlights: Sixty papers using transplanted macroalgae in biomonitoring studies were reviewed. The methodological aspects of the transplant technique were evaluated. Uniform techniques have not been used which hampers comparison of results among studies. A protocol for routine biomonitoring of the quality of coastal waters is proposed.